Traffic grooming in WDM mesh networks - Zhang, Zhichao. (2008)
To effectively groom static traffic requests in a more general optical mesh network in order to minimize the network cost in terms of the number of optoelectronic transceivers. This is achieved by using the proposed Revised Shortest Path Algorithm (RSPA).